2008
DOI: 10.1038/clpt.2008.236
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir Pharmacokinetics During Chronic Therapy in HIV-1-Infected Adolescents and Young Adults

Abstract: The pharmacokinetics of abacavir and its metabolites were investigated in 30 human immunodeficiency virus (HIV)-infected adolescents and young adults 13-25 years of age, equally divided into two groups: <18 years of age and ≥18 years of age. All the subjects received the recommended adult dose of 300 mg twice daily. The area under the plasma concentration-time curve (AUC) and half-life of abacavir did not differ significantly between the age groups or by gender or race, and there were only modest associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…However, interestingly, although lamivudine doses received were 17% higher, children in our ARROW Trial PK study had lamivudine AUC 0-24 and C max values that were 33% and 52% higher, respectively, on once-daily dosing compared with those observed in PENTA 13, whereas CL/F/kg values were 10% lower in the ARROW Trial PK study (a similar observation was made for twice-daily dosing; Table 3). PK parameters in the ARROW Trial PK study were also generally more similar to those previously observed in adults (for example, ARROW Trial PK study AUC 0-24 values on twice-daily dosing were only 8% higher than a recent study in Ugandan adults [20], 12% lower than a study in adolescents and young adults [21]; however, findings from two other adult twice-to once-daily studies have been more variable, with results 30% higher [22] and 30% lower [8] than our study). Of note, 14 of 19 children in PENTA 13 were taking lamivudine syrup, dosed at 8 mg/kg daily, whereas all ARROW Trial children were taking scored adult tablets, with a 15-17% higher average dose (32/35 and 29/35 on twice-and once-daily, respectively, achieving ≥8 mg/kg).…”
Section: Lamivudinesupporting
confidence: 73%
“…However, interestingly, although lamivudine doses received were 17% higher, children in our ARROW Trial PK study had lamivudine AUC 0-24 and C max values that were 33% and 52% higher, respectively, on once-daily dosing compared with those observed in PENTA 13, whereas CL/F/kg values were 10% lower in the ARROW Trial PK study (a similar observation was made for twice-daily dosing; Table 3). PK parameters in the ARROW Trial PK study were also generally more similar to those previously observed in adults (for example, ARROW Trial PK study AUC 0-24 values on twice-daily dosing were only 8% higher than a recent study in Ugandan adults [20], 12% lower than a study in adolescents and young adults [21]; however, findings from two other adult twice-to once-daily studies have been more variable, with results 30% higher [22] and 30% lower [8] than our study). Of note, 14 of 19 children in PENTA 13 were taking lamivudine syrup, dosed at 8 mg/kg daily, whereas all ARROW Trial children were taking scored adult tablets, with a 15-17% higher average dose (32/35 and 29/35 on twice-and once-daily, respectively, achieving ≥8 mg/kg).…”
Section: Lamivudinesupporting
confidence: 73%
“…These datasets were pooled from nine published studies: therapeutic drug monitoring data from France, the BURKINAME -Agence Française de [15][16][17][18][19][20].…”
Section: Lamivudinementioning
confidence: 99%
“…The data consisted of five pooled studies, that is, four previously published studies: therapeutic drug monitoring from France, Paediatric European Network for Treatment of AIDS (PENTA) protocol PENTA 13 from United Kingdom, IMPAACT/PACTG 1018, 1052 protocols from United States plus PACTG 356 with ABC pharmacokinetic samples obtained pre-dose as well as 1 to 3 h and 4 to 6 h post-dose from the US [15][16][17][18][19][20].…”
Section: Abacavirmentioning
confidence: 99%
“…Elimination of abacavir occurs via metabolism by alcohol dehydrogenase (to form 5′-carboxylic acid) and glucuronyl transferase (to form 5′-glucuronide) [11], and in vitro data indicate that abacavir does not inhibit CYP3A4, CYP2D6 or CYP2C9 activity at clinically relevant concentrations [12]. However, abacavir is known to be a substrate for UGT2B7 [13], suggesting that lersivirine has the potential to increase exposures of abacavir via UGT2B7 inhibition. The majority of lamivudine is eliminated unchanged in urine by active organic cationic secretion [11]; therefore, the potential for lersivirine to affect lamivudine exposure is low.…”
Section: Original Articlementioning
confidence: 99%